2014
DOI: 10.1039/c3cp54535k
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of PNIPAmx-PEO20-PPO70-PEO20-PNIPAmx pentablock terpolymer on gold surfaces: effects of concentration, temperature, block length, and surface properties

Abstract: The effects of concentration, relative block length and environmental temperature as well as the surface chemical and wetting properties of solid substrates on the adsorption behaviors and mechanisms of a series of pentablock terpolymer poly(N-isopropylacrylamide)x-poly(ethylene oxide)20-poly(propylene oxide)70-poly(ethylene oxide)20-poly(N-isopropylacrylamide)x (PNIPAmx-PEO20-PPO70-PEO20-PNIPAmx or PNIPAmx-P123-PNIPAmx) with x of 10, 63 and 97 on gold were studied by using a quartz crystal microbalance (QCM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…[18][19][20] In principle, this type of technique can detect the adsorption, conformation and interactions of macromolecules at an interface. [21][22][23] For instance, Du and colleagues 24,25 investigated the adsorption of block copolymers on a gold (Au) surface using a QCM technique. The results indicated that the adsorption mechanism of a PNIPAm x -P123-PNIPAm x pentablock terpolymer was mainly determined by the interactions between the pentablock terpolymers molecules with different chain conformations in dilute aqueous solutions at various temperatures and the Au substrates with surface wetting and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] In principle, this type of technique can detect the adsorption, conformation and interactions of macromolecules at an interface. [21][22][23] For instance, Du and colleagues 24,25 investigated the adsorption of block copolymers on a gold (Au) surface using a QCM technique. The results indicated that the adsorption mechanism of a PNIPAm x -P123-PNIPAm x pentablock terpolymer was mainly determined by the interactions between the pentablock terpolymers molecules with different chain conformations in dilute aqueous solutions at various temperatures and the Au substrates with surface wetting and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…With addition of a third block C, more than 30 different phase structures have been identified for ABC-type linear triblock terpolymers, including four traditional phases: lamellae, cylinders, spheres, and gyroid as well as some other special hierarchical structures, such as the ring on cylinder, cylinder on lamellae, and knitting pattern . In recent years, the chemical and physical properties as well as self-assembly behaviors of BCPs with more complicated block architectures, including ABAC-type and ABCA-type tetrablocks, ABCBA pentablocks, and other multiblock terpolymers, have increasingly attracted the experimental and theoretical attention of the research community. The multiblock copolymers have various structural parameters such as the number of blocks, block sequence, monomer types, functionality, and composition.…”
Section: Introductionmentioning
confidence: 99%
“…The symmetric linear ABCBA pentablock terpolymers have been considered as the simplest model system of multiblock copolymers and the excellent candidate for exploring the structures and properties of multiblock copolymers. However, most investigations of ABCBA pentablock terpolymers were focused on the synthesis methods, micellization in solutions, and stimuli-sensitive behaviors in solvent. , Only a few studies have reported experimentally and theoretically on the phase behaviors of ABCBA pentablock terpolymers in bulk. Kopchick et al have reported that poly­(acrylic acid- b -styrene- b -isobutylene- b -styrene- b -acrylic acid) pentablock terpolymers formed three-phase morphologies with a considerable order.…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed different behaviors of the adsorbed polymer depending on its state of adsorption, e.g., whether chemisorbed [50,51] or physisorbed [52,53]. The adsorption of thermosensitive block copolymers based on PNIPAAm on a gold surface was also investigated by QCM-D [54]. For example, the adsorption mechanism of a pentablock terpolymer poly (N-isopropylacrylamide)x-block-poly (ethylene oxide) 20 SP is one of the chromophores that is not only a photo-switch but also responds to other stimuli such as temperature, solvent, metal ions, and pH [41].…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed different behaviors of the adsorbed polymer depending on its state of adsorption, e.g., whether chemisorbed [ 50 , 51 ] or physisorbed [ 52 , 53 ]. The adsorption of thermosensitive block copolymers based on PNIPAAm on a gold surface was also investigated by QCM-D [ 54 ]. For example, the adsorption mechanism of a pentablock terpolymer poly ( N -isopropylacrylamide) x - block -poly (ethylene oxide) 20 - block -poly (propylene oxide) 70 - block -poly (ethylene oxide) 20 - block -poly ( N -isopropylacrylamide) x (PNIPAAm x - b -PEO 20 - b -PPO 70 - b -PEO 20 - b -PNIPAAm x ) on gold was found to be affected by several parameters including concentration, relative block length, temperature, and the substrate’s physical properties.…”
Section: Introductionmentioning
confidence: 99%